Sistem Pembentuk Struktur Ruang Rumah Masyarakat Adat Suku Moronene Kampo Laea Hukaea, Kabupaten Bombana,Sulawesi Tenggara - Adriyawan Jarsul Hamasi; T. Yoyok Wahyu Subroto (Arsir: Jurnal Arsitektur, 2025)
Kampo Laea Hukaea is the indigenous territory of the Moronene tribe, one of the native tribes of Southeast Sulawesi Province. Within this area, there are traditional buildings of the Moronene tribe that have not been studied, and their quality has been deteriorating according to the local community. This threatens the authenticity and identity of the Moronene tribe. This research aims to identify the spatial structure formation system of the Moronene people's houses in Kampo Laea Hukaea. Using a descriptive qualitative method, with direct field observation and in-depth interviews, data was collected and analyzed through triangulation. The research findings reveal that the Moronene people's houses have a spatial structure divided both horizontally and vertically. Horizontally, there are the patande space (included in laica irai or front house), botono space (the core of the house), and the dapura space (included in laica ibungku or back house). Vertically, there are the tonto space (lower section), botono space (middle section), and pea space (upper section). These spaces, both horizontally and vertically, are consistently found in the cases, thus forming the spatial structure system in the houses of the Moronene people, which is an authentic identity of the Moronene tribe's culture in Kampo Laea Hukaea. This study contributes to uncovering the identity of the traditional houses of the Moronene people, thereby enhancing the sense of responsibility toward preserving ancestral heritage and maintaining the Kampo Laea Hukaea environment.